Pengaruh Kepemimpinan dan Lingkungan Kerja Terhadap Kinerja Aparatur Sipil Negara (ASN) di Sekretariat Daerah Kabupaten Gowa - Rifkah Pardawiyanti P; Agung Widhi Kurniawan; Burhanuddin Burhanuddin; Abdi Akbar; Uhud Darmawan Natsir (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
The purpose of this research is to ascertain how the work environment and leadership affect the performance of Civil Servants (ASN) in the Gowa Regency Regional Secretariat. This study uses a quantitative approach. Civil Servants (ASN) and non-ASN workers make up the population. 50 respondents make up the sample size as a consequence of the statistical sampling methodology combined with the random selection method. Techniques for gathering data include surveys, recordkeeping, and observation. Using SPSS version 30, multiple linear regression analysis and traditional assumption tests were the data analysis techniques used in this investigation.The findings indicate that the performance of ASN in the Gowa Regency Regional Secretariat is positively and significantly impacted by the leadership variable. The ASN in the Gowa Regency Regional Secretariat is positively and significantly impacted by the work environment variable. The ASN in the Regional Secretariat of Gowa Regency is positively and significantly impacted by leadership and work environment factors at the same time.